2019
DOI: 10.1177/1468087419865384
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of piston bowl and valve system in compression ignition engine fueled with gasoline/diesel/polyoxymethylene dimethyl ethers for high efficiency

Abstract: Polyoxymethylene dimethyl ethers, with excellent volatility and oxygen content of up to 49%, have great potential to improve engine performance and emission characteristics. In this study, experiments were carried out in a single-cylinder engine fueled with gasoline/diesel/polyoxymethylene dimethyl ethers blend fuel using multiple premixed compression ignition combustion mode along with engine optimization to exploit the high-efficiency potential. The thermal efficiency was increased by 9.4 percentage points a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…However, with increasingly stringent emissions regulations, seeking environmentally friendly fuels for diesel engines is of urgency. Studies have shown that the usage of oxygenated alternative fuels can improve diesel engines’ combustion and emissions performance, without significantly affecting their power output [1] , [2] , [3] .…”
Section: Introductionmentioning
confidence: 99%
“…However, with increasingly stringent emissions regulations, seeking environmentally friendly fuels for diesel engines is of urgency. Studies have shown that the usage of oxygenated alternative fuels can improve diesel engines’ combustion and emissions performance, without significantly affecting their power output [1] , [2] , [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, PODE 3 has a very high CN, which can potentially overcome the drawbacks of GD blends when gasoline/diesel/ PODE 3 (GDP) blends are applied. 129 Moreover, with the soot reduction potential expected of PODE 3 , GDP blends can be anticipated to further reduce soot emissions, possibly forming ideal concoctions for clean combustion. Liu et al 1 experimentally investigated GDP blends and realized GDP blends produce less HC, CO and soot emissions as compared to GD blends.…”
Section: Numerical Investigationmentioning
confidence: 99%
“…The main goal is to achieve an engine with lower emissions and higher efficiency. [1][2][3] Among the solutions that are being explored to improve thermal efficiency, one is the development of innovative insulating materials to coat some engine parts, [4][5][6] such as the combustion chamber walls and the exhaust pipes manifold. However, the real global impact of coating these surfaces on the final engine performance is not clear.…”
Section: Introductionmentioning
confidence: 99%